2006
DOI: 10.1007/s00414-006-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Hungarian mtDNA population databases from Budapest and the Baranya county Roma

Abstract: To facilitate forensic mtDNA testing in Hungary, we have generated control region databases for two Hungarian populations: 211 individuals were sampled from the urban Budapest population and 208 individuals were sampled from a Romani ("gypsy") population in Baranya county. Sequences were generated using a highly redundant approach to minimize potential database errors. The Budapest population had high sequence diversity with 180 lineages, 183 polymorphic positions, and a random match probability of 1%. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…Finnish (Simoni et al 2000) 28 Italian, Tuscany (Simoni et al 2000) 29 Sicilian (Simoni et al 2000) 30 Norwegian (Simoni et al 2000 (Irwin et al 2007) 54 Szekler (Brandstätter et al 2007) 55 Csango (Brandstätter et al 2007) 56 Dutch (http://www. eupedia.com) population groups (3 Mongolian, Evenki, Kyrgyz and Chinese populations) were grouped into cluster VI (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finnish (Simoni et al 2000) 28 Italian, Tuscany (Simoni et al 2000) 29 Sicilian (Simoni et al 2000) 30 Norwegian (Simoni et al 2000 (Irwin et al 2007) 54 Szekler (Brandstätter et al 2007) 55 Csango (Brandstätter et al 2007) 56 Dutch (http://www. eupedia.com) population groups (3 Mongolian, Evenki, Kyrgyz and Chinese populations) were grouped into cluster VI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To compare maternal lineages, we used published mtDNA haplogroup frequencies Bosch et al 2006;Brandstätter et al 2007;Comas et al 2004;Derbeneva et al 2002;Helgason et al 2001;Irwin et al 2007;Maca-Meyer et al 2003;Malyarchuk et al 2002;Merriwether et al 1996;Pakendorf et al 2007;Passarino et al 2002;Pericić et al 2005a;Pimenoff et al 2008;Quintana-Murci et al 2004;Simoni et al 2000;Starikovskaya et al 2005;Yao et al 2004; http://www. eupedia.com).…”
Section: Methods For Genetic Analysismentioning
confidence: 99%
“…For many populations, however, large forensic mtDNA databases that cover the entire control region and adhere to strict guidelines in terms of their generation and maintenance are not available. A number of recent publications reflect largescale efforts to augment global forensic mtDNA databases with high-quality, entire control region data [1][2][3][4][5][6]. In line with these efforts, we present entire control region data from two populations: Greeks from northern Greece and Greek Cypriots.…”
Section: Introductionmentioning
confidence: 94%
“…Malyarchuk et al [12] analyzed the control region segment of a sample of Polish Roma, and the mitogenome of a Polish donor carrying a M5 Roma lineage; their study also indicated the existence of mtDNA founder effects in the Polish Roma. Over the last few years, other Romani populations have been analyzed, including individuals from Hungary, Romania, Slovakia and Poland [13] [14] [15] [16] [17]. Regarding uniparental markers, a recent Y-chromosome study by Regueiro et al [18] claims that the Roma descended from southern Indian populations, thereby contradicting various reports based on mtDNA and autosomal studies (see below) that pointed to northwest India as the homeland of proto-Romani.…”
Section: Introductionmentioning
confidence: 99%